2019
DOI: 10.1007/s11468-019-01019-3
|View full text |Cite
|
Sign up to set email alerts
|

Localized Surface Plasmon Resonances of Simple Tunable Plasmonic Nanostructures

Abstract: We derive and present systematic relationships between the analytical formulas for calculation of the localized surface plasmon resonances (LSPR) of some plasmonic nanostructures which we have categorized as simple. These relationships, including some new formulas, are summarized in a tree diagram which highlights the core-shell plasmons as the generators of solid and cavity plasmons. In addition, we show that the LSPR of complex structures can be reduced to that of simpler ones, using the LSPR of a nanorice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Likewise, the aspect ratio of a nanorod (NR) enables its LSPR to be tuned with great sensitivity along the longitudinal axis [8][9][10][11][12][13][14][15] . Both the longitudinal dipolar LSPR of a NR 8,[14][15][16][17][18] and the dipolar LSPR of a NE 4,5 have a common property, namely a redshift in their LSPR with an increase in their respective asymmetry parameters, i.e., the aspect ratio of the NR and the core-offset of the NE. When these two nanoparticles are spatially separated by a small gap, a NE-NR heterodimer is formed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the aspect ratio of a nanorod (NR) enables its LSPR to be tuned with great sensitivity along the longitudinal axis [8][9][10][11][12][13][14][15] . Both the longitudinal dipolar LSPR of a NR 8,[14][15][16][17][18] and the dipolar LSPR of a NE 4,5 have a common property, namely a redshift in their LSPR with an increase in their respective asymmetry parameters, i.e., the aspect ratio of the NR and the core-offset of the NE. When these two nanoparticles are spatially separated by a small gap, a NE-NR heterodimer is formed.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that plexcitonic systems exhibit EIT 49? ,50 due to the interaction between excitonic resonances of molecular aggregates 50,51 and LSPR of metallic nanostructures 18,49,52 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photothermal effect of metal-bearing nanomaterials is caused by the localized surface plasmon resonance (LSPR) generated when they are exposed to specific wavelengths of light. The size, shape, and composition of metal-bearing nanomaterials can affect their excitation wavelengths and thus their LSPR and photothermal activity. For example, increasing the size of nanomaterials can increase their excitation wavelengths. Irregularly shaped nanomaterials possess multiple excitation wavelengths due to allowing electron clouds to be polarized in different ways.…”
Section: External Stimuli-activated On-demand Antibacterial Strategiesmentioning
confidence: 99%
“…Noble metal nanoparticles (MNPs) have appealed researchers a lot with respect to the fundamental as well as emerging applied research because of their fascinating optical properties [1][2][3]. The exciting optical properties appear because of the well-known phenomenon of localized surface plasmon resonance (LSPR) which is the result of coherent oscillation of free electron density at the metal-dielectric interface at the expense of the incident light energy.…”
Section: Introductionmentioning
confidence: 99%